Development and characterization of polysiloxane-based gel loaded with phytoingredients encapsulated in phytosomes for scar management: Polysiloxane gel containing phyto-materials for scar treatment - Naseriyeh, Tahereh; Kahrizi, Danial; Arkan, Elham; Moradi, Sajad; Kahrizi, Farzad (Cellular and Molecular Biology, 2024)
Recent research has emphasized the development of efficient drug delivery systems to facilitate the delivery of biological compounds such as polyphenols via skin absorption. Phytozomes have been employed as carriers of plant compounds in this context Hydrogen bonding between plant polyphenols and the phospholipid phosphate group enables efficient encapsulation of potent compounds for enhanced drug delivery systems. Additionally, the strong affinity of phytosomes for the skin's phospholipids enhances skin absorption. In this study, phytosomes were initially formulated using the thin-layer hydration method After optimizing the synthetic parameters, phytosomes were loaded with Resveratrol and Quercetin for enhanced delivery and skin absorption potential to assess the characteristics of the synthesized phytosomes, tests were conducted to determine particle distribution and size, zeta potential, and examine the microstructure morphology using a scanning electron microscope (SEM). Furthermore, a siloxane gel base was formulated in this study, and the stability of the physicochemical and biological properties of the final prepared nanoformulation was investigated. The results of this study indicated that the formulated phytosomes exhibit optimal characteristics for facilitating high skin penetration of resveratrol and quercetin. A high skin absorption was observed after 60 days of synthesis. Additionally, the base of the siloxane gel can play a significant role in preventing the formation of scars by reducing the passage of water vapor.